A surface analytical investigation of cerium‐based conversion coatings deposited onto an AA2024‐T3 aluminium alloy cladding layer1. (24th April 2014) - Hinder, S. J.; Grilli, R.; Rustame, M.; Santos, W. I. A.; Baker, M. A.; Costa, I.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> Cerium‐based conversion coatings are being investigated as alternatives to chromating treatments for the corrosion protection of aluminium and its alloys because of the environmentally unfriendly nature of the chromating process. This study investigates the surface film composition, structure and corrosion performance following a two‐step surface treatment for an AA2024‐T3 clad aluminium alloy. The two‐step treatment comprised of an initial cerium conversion process involving immersion in an aqueous solution containing Ce3+ ions at 75 °C followed by immersion in a propylene glycol solution at 75 °C. The coating surface morphology, composition and structure have been studied using SEM, XPS, Auger spectroscopy and Fourier transform infrared spectroscopy, while corrosion resistance was evaluated using electrochemical impedance spectroscopy. The coating formed by the two‐step treatment is an interconnecting fibrous (pseudo) boehmite layer with the incorporation of Ce3+ in the film. This two step treatment coating exhibits high impedance compared with the coatings formed through exposure to just stage 1 or stage 2 of the two‐step treatment and shows good potential for improved corrosion protection. Copyright © 2014 John Wiley & Sons, Ltd.